The Role of Notaries in the Company Acquisition Process - Nugroho, Bagus Susilo (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
.This study aims to determine the role of a notary in the acquisition process in a palm oil company. At present there are more and more palm oil companies in Indonesia, which makes competition between palm oil companies even tighter, so that the turnover of existing capital is not always smooth. That's why it is possible to make acquisitions for the purpose of business advantage. The approach method used in this study is an empirical juridical approach, namely studying the applicable legal provisions and what actually happens in society. Acquisitions are divided into two types, namely based on the object to be taken over and the type of business or businesses that have their respective procedures. The role of the notary in the acquisition starts from the beginning of the acquisition process, namely since the General Meeting of Shareholders (GMS) was held to obtain approval for the acquisition where the notary was always involved in making the deed of the GMS. Based on the results of the GMS, if the acquisition has received approval from the shareholders, the notary can prepare the acquisition deed. In addition to preparing the deed of GMS and deed of acquisition, the role of the notary in acquisitions is to provide services in the form of managing the validity of the acquisition, especially regarding the ratification of changes to the company's articles of association as a result of the acquisition to the competent authority (Ministry of Law and Human Rights). So it can be concluded that acquisitions in palm oil companies have a business goal to save the company and the Notary plays an important role in the processes that occur therein.